Exchangeable copper: a reflection of the neurological severity in Wilson's disease. (14th October 2016) - Poujois, A.; Trocello, J.‐M.; Djebrani‐Oussedik, N.; Poupon, J.; Collet, C.; Girardot‐Tinant, N.; Sobesky, R.; Habès, D.; Debray, D.; Vanlemmens, C.; Fluchère, F.; Ory‐Magne, F.; et al.
Abstract : Background and purpose: The severity of Wilson's disease (WD) is linked to free copper accumulating in the liver and brain. Exchangeable copper (CuEXC) is a new technique to determine plasmatic copper and is useful in the diagnosis of WD. It is hypothesized that it may also enable a good evaluation of extra‐hepatic involvement and its severity. Methods: Forty‐eight newly diagnosed WD patients were prospectively evaluated using hepatic, neurological, ophthalmological and brain magnetic resonance imaging (MRI) scores. Three phenotypic presentations were distinguished: pre‐symptomatic, hepatic and extra‐hepatic. CuEXC was determined in addition to standard copper assays before decoppering therapy. Correlations between biological parameters and the different scores were determined and compared in the hepatic and extra‐hepatic groups. Results: Extra‐hepatic patients had significantly higher CuEXC values than those with the hepatic form ( P < 0.0001). The overall ability of CuEXC to separate the two forms was satisfactory, with an area under the curve of 0.883 (95% confidence interval 0.771–0.996) and an optimal threshold for extra‐hepatic diagnosis of 2.08 μmol/l (sensitivity 85.7%; specificity 94.1%). In extra‐hepatic patients, CuEXC was the only biological marker to be positively correlated with the Unified Wilson Disease Rating Score ( r = 0.45, P = 0.016), the Kayser−Fleischer ring score ( r = 0.46, P = 0.014) and the brain MRI score ( r = 0.38, P = 0.048), but it was not correlated with the hepatic score. Conclusions: Exchangeable copper determination is useful when diagnosing WD as a value >2.08 μmol/l is indicative of the severity of the extra‐hepatic involvement. In the case of purely hepatic presentation, atypical or mild neurological signs, it should encourage physicians to search for lesions in the brain and eyes.